Pelatihan Penyusunan Program Kerja dalam Mengoptimalkan Peran Dewan Pendidikan - Achmad Supriyanto; Burhanuddin Burhanuddin; Ludi Wishnu Wardana; Asep Sunandar; Nur Luthfi Ardhian; Karine Rizkita (Abdimas Pedagogi: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Abstract: This community service article aims to describe the results of training in the preparation of work programs in optimizing the role of the education board. Methods The implementation of this activity is in the form of education and training through workshops. The location of the activity is at the Mojokerto Regency Education Council office. The target of this activity consisted of the administrators of the Mojokerto Regency Education Council and several representatives from lower levels. The number is 11 people. The stages of implementing this activity include: (1) the implementation of this activity using an educational approach and workshop training. Data were collected during the activity using observation and interview techniques. The analysis uses a qualitative approach by finding a tendency to conclude. The results of the workshop can be in the form of a work program for the Board of Education that will be implemented in the future. The results of the implementation of the activities showed that the workshop was able to improve, (1) the ability of the activity participants in preparing the work program of the education council, (2) the results of the preparation of the resulting work program could increase the optimization of the role of the education council in advancing education, but it was not optimal. Abstrak: Artikel pengabdian kepada masyarakat ini bertujuan untuk menggambarkan hasil pelatihan penyusunan program kerja dalam mengoptimalkan peran dewan pendidikan. Metode Pelaksanaan kegiatan ini berupa pendidikan dan pelatihan melalui workshop. Lokasi kegiatan di kantor Dewan Pendidikan Kabupaten Mojokerto. Sasaran kegiatan ini terdiri dari para pengurus Dewan Pendidikan Kabupaten Mojokerto dan beberapa perwakilan dari tingkat di bawahnya yang berjumlah 11 orang. Pelaksanaan kegiatan ini menggunakan pendekatan pendidikan dan pelatihan workshop. Data dikumpulkan pada saat kegiatan dengan teknik observasi dan wawancara. Analisisnya menggunakan pendekatan kualitatif dengan menemukan kecenderungan untuk disimpulkan. Hasil workshop berupa program kerja Dewan Pendidikan yang akan dilaksanakan di masa mendatang. Hasil pelaksanaan kegiatan menunjukkan bahwa melalui workshop mampu ditingkatkan (1) kemampuan peserta kegiatan dalam penyusunan program kerja dewan pendidikan dan (2) optimalisasi peran dewan pendidikan dalam memajukan pendidikan (meskipun belum maksimal) sebagai hasil dari penyusunan program kerja.